👤

Bonjour pouvez vous m'aider svp en equation :

Factoriser :

a. (6x+2) (-5x+4) -3 (6x+2)

b. (5x-3) (2x+9) + 5x-3

c. (-5x-2)² + (-5x-2) (6x+6)

Merci de votre aide - Bonne fin de journée


Répondre :

Réponse :

Explications étape par étape

Bonjour

Factoriser :

a. (6x+2) (-5x+4) -3 (6x+2)

= (6x + 2)(-5x + 4 - 3)

= (6x + 2)(-5x + 1)

= 2(3x + 1)(-5x + 1)

b. (5x-3) (2x+9) + 5x-3

= (5x - 3)(2x + 9 + 1)

= (5x - 3)(2x + 10)

= (5x - 3) * 2(x + 5)

= 2(5x - 3)(x + 5)

c. (-5x-2)² + (-5x-2) (6x+6)

= (-5x - 2)(-5x - 2 + 6x + 6)

= (-5x - 2)(x + 4)

Réponse :

a. (6x+2) (-5x+4) -3 (6x+2)

(6x+2)(-5x+4-3)=

(6x+2)(-5x+1)=

2(3x+1)(-5x+1)

b. (5x-3) (2x+9) +(5x-3)=

(5x-3)(2x+9)+1(5x-3)

(5x-3)(2x+9+1)=

(5x-3)(2x+10)=

2(5x-3)(x+5)

c. (-5x-2)² + (-5x-2) (6x+6)=

(-5x-2)(-5x-2+6x+6)=

(-5x-2)(x+4)

Explications étape par étape